Incidence of fair trade in agri-food development in the ethnic territories of North Cauca: Case of banana production in Padilla, Cauca - Escobar Quiñonez, Edward Enrique (Cooperativismo & Desarrollo, 2020)
The proposal is to analyze whether there is development of the agrifood sector through fair trade, this study will be conducted with ethnic population of the region of North Cauca - Colombia, in the measurement method, will apply various instruments such as surveys of peasant communities, complementary to this secondary information in statistical databases of the various actors as leaders, rural entrepreneurs and community in general, all directly. For them, a description of the current state of agrarian policy in Colombia will be made, as well as identifying the regulations that promote the application of Fair Trade in the ethnic territories of the North of Cauca, adding the comparison of fair trade practices in the Latin American context, and identifying and analyzing the social and economic practices that have influenced the development of Fair Trade, in order to recommend economic development strategies that enhance the improvement of productive practices in the ethnic territories of the region.
Keywords: economic development; local development; solidarity economy; agrarian policy